Evaluation of a Burkholderia ambifaria strain from plants as a novel promising probiotic in dental caries management - Zirang Chen; Yangyu Lu; Zhezhen Xu; Lijing Wu; Xi Wei; Yanling Cai (Journal of Oral Microbiology)
Background Probiotics serve as a novel preventive or therapeutic approach for dental caries owing to their ability to reverse dysbiosis and restore a healthy microbiota. Here, we identified Burkholderia ambifaria AFS098024 as a probiotic candidate isolated from plants.Methods The safety of B. ambifaria was evaluated by hemolytic activity, D-lactic acid production and antibiotic susceptibility. In vitro biofilm model derived from the saliva of caries-free and caries-active donors and in vivo rat caries model were used to assess the efficacy of B. ambifaria in caries prevention and treatment.Results B. ambifaria was safe as a probiotic candidate and it could integrate with in vitro biofilm model. It significantly reduced the biomass and lactate production of biofilms from caries-active donors and disrupted biofilm structures. B. ambifaria effectively reduced the severity of carious lesions in rat molars, regardless of the inoculation sequence. Molars pretreated or treated with B. ambifaria demonstrated notably higher enamel volumes. Additionally, colonization of rat molars by B. ambifaria persisted for 6 weeks.Conclusion The B. ambifaria strain used in this study holds promise as a probiotic for inhibiting dental caries, both in vitro and in vivo.